Serum CYFRA 21.1 Level Predicts Disease Course in Thyroid Cancer with Distant Metastasis - Jeong, Chaiho; Lee, Jeongmin; Yoon, Hyukjin; Ha, Jeonghoon; Kim, Min-Hee; Bae, Ja-Seong; Jung, Chan-Kwon; Kim, Jeong-Soo; Kang, Moo-Il; Lim, Dong-Jun (Cancers, 2021)
Background: Serum Cyfra 21.1, the soluble fragment of CK19, has been used as a prognostic tumor marker in various cancers, indicating poor tumor differentiation and increased metastasis. Methods: We analyzed the serum Cyfra 21.1 level in 51 consecutive patients with thyroid cancer manifesting distant metastasis treated with prior total thyroidectomy. Serum Cyfra 21.1 levels of 26 thyroid cancer patients without metastasis and 50 healthy individuals were used for comparison. Results: Higher serum Cyfra 21.1 levels were detected in thyroid cancer patients with distant metastasis compared with healthy subjects and thyroid cancer patients without metastasis (p = 0.012). Serum Cyfra 21.1 levels were significantly increased in patients with positive BRAF V600E mutation (p = 0.019), undergoing Tyrosine Kinase Inhibitor (TKI) therapy (p = 0.008), with radioiodine-refractory status (p = 0.047), and in disease progression compared with those manifesting stable disease (p = 0.007). In progressive disease with undetectable or unmonitored thyroglobulin because of thyroglobulin antibody, serum Cyfra 21.1 was useful as a biomarker for follow-up of disease course. Conclusion: Serum Cyfra 21.1 in thyroid cancer patients might represent an alternative biomarker predicting tumor progression, especially in cases not associated with serum Tg levels.